Entrepreneurship, polycentrism, and elites : local industrial development in modern Italy - Carboni, Carlo, 1952-; Orazi, Francesco (Abingdon, Oxon ; New York, NY : Routledge, 2021)
The book is a cross-section of the over all Italian development. Italy can be considered a microcosm that contains all the imbalances and territorial differences that can be observed in the European macro-areas. Its north can now be considred integrated with the more developed European continental shelf. The Centre represents a local development in transition to a more visible technological change. The late south risks accumulating more socio-economic backwardness. For these reasons, we believe this volume is useful, with just a few pages presenting one of the most interesting cases of local industrial development, outside the mainstream of the industrial economy which saw in Fordism and Taylorism the best way for industrializaion. Here, on the contrary, it is argued that big fish cannot always consume the smallest one that flickers faster and its flexibility, that has social roots, can be an advantage in global markets. Technology appears to be the key to the future. Please note: This title is co-published with Aakar Books, New Delhi. Print edition not for sale in South Asia (India, Sri Lanka, Nepal, Bangladesh, Pakistan, Maldives or Bhutan)
3.7 Political Autonomy without Economic Development: The Eclipse of Decentralization -- Conclusion -- Afterword
OCLC-licensed vendor bibliographic record.
Keywords: Industrialization -- Italy; Economic development -- Italy; Entrepreneurship -- Italy; Technology -- Economic aspects -- Italy; Italy -- Economic conditions; Italy -- Social conditions; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Development / Economic Development; BUSINESS & ECONOMICS / Government & Business